Curcumin Modulates the Crosstalk Between Macrophages and Bone Mesenchymal Stem Cells to Ameliorate Osteogenesis - Chen, Songfeng; Liang, Hang; Ji, Yanhui; Kou, Hongwei; Zhang, Chi; Shang, Guowei; Shang, Chunfeng; Song, Zongmian; Yang, Lin; Liu, Lei; Wang, Yongkui; Liu, Hongjian (Frontiers in Cell and Developmental Biology, 2021)
Bone healing is thought to be influenced by the cross-talk between bone forming and immune cells. In particular, macrophages play a crucial role in the regulation of osteogenesis. Curcumin, the major bioactive polyphenolic ingredient of turmeric, has been shown to regulate inflammatory response and osteogenic activities. However, whether curcumin could regulate macrophage polarization and subsequently influence osteogenesis remain to be elucidated. In this study, the potential immunomodulatory capability of curcumin on inflammatory response and phenotype switch of macrophages and the subsequent impact on osteogenic differentiation of MSCs are investigated. We demonstrated that curcumin exhibited significant anti-inflammatory effect by polarizing the macrophages towards anti-inflammatory phenotype, with increased expression of IL-4, IL-10 and CD206, and decreased expression of IL-1β, TNF-α, CCR7 and iNOS. In addition, curcumin could improve the osteo-immune microenvironment via promoting osteogenesis-related regenerative cytokine BMP-2 and TGF-β production. Moreover, the co-cultured test of macrophages and BMSCs showed that curcumin-modulated macrophages conditioned medium could promote osteogenic differentiation of BMSCs with increased gene (ALP, Runx-2, OCN, and OPN) and protein (Runx-2 and OCN) expression levels, enhanced ALP activity and obvious formation of mineralized nodules. Taken together, with the interaction between curcumin-conditioned macrophage and curcumin-stimulated BMSCs, curcumin could remarkably enhance the osteogenic differentiation of BMSCs in LPS-activated inflammatory macrophage-BMSCs coculture system.